Transformation Of The Media Economy Of The News Site Jawapos.Com In The Digital Era - Yunianto, Ibnu (Universitas 17 Agustus 1945 Surabaya, 2024)
The development of information technology and communication technology causes disruption reducing the media's ability to earn revenue, retain audiences, and producing quality content that threatens its survival. The effects of disruption were also felt by print-based media conglomerates such as Jawa Pos in the form of a decline in revenue from circulation and advertising turnover. Business diversification into a digital business with a vertical expansion and vertical merger model was carried out to build the Jawa Pos Multimedia Group subsidiary as a digital conglomerate. This research uses media ecology theory and Robert G. Picard's media economics perspective to explain how media companies maintain business continuity in the era of digitalization and explaining the results of the media economic transformation in the aspect of media sustainability. Based on the research results, the practice of continuum convergence, journalistic convergence, and cross selling and co-promotion strategies were able to change the company managing the JawaPos.com news site from a loss-making condition in 2017 to a profit in the 2021 financial year. This research also found that the survival of the media is not only determined by the quality of journalistic products, but also success in market penetration, financial management, and effective and efficient human capital management.